2008
DOI: 10.2319/050207-212.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts on Daily Performances Related to Wearing Orthodontic Appliances

Abstract: Objective: To assess the prevalence, intensity, and extent of the impacts on daily performances related to wearing different types of orthodontic appliances. Materials and Methods: A total of 1657 students, 15 to 16 years old, were randomly selected from those attending all secondary schools in Bauru, Sã o Paulo, Brazil. Only those wearing orthodontic appliances at the time of the survey were included. Face-to-face structured interviews were done to collect information about impacts on quality of life related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 22 publications
8
57
2
1
Order By: Relevance
“…A previous research in adolescents found that specific impacts on daily living, related to wearing orthodontic appliances, were higher among patients wearing FOA compared to those wearing removable appliances 21. Relying on the similar baseline before treatment in both the groups, our study also found similar results on the impacts of orthodontic appliances on eating, cleaning teeth, smiling, working, and social relation in daily life; the impacts were significantly weaker in patients wearing clear-aligner.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A previous research in adolescents found that specific impacts on daily living, related to wearing orthodontic appliances, were higher among patients wearing FOA compared to those wearing removable appliances 21. Relying on the similar baseline before treatment in both the groups, our study also found similar results on the impacts of orthodontic appliances on eating, cleaning teeth, smiling, working, and social relation in daily life; the impacts were significantly weaker in patients wearing clear-aligner.…”
Section: Discussionsupporting
confidence: 83%
“…This supports earlier findings that a patient’s OHRQoL is frequently worse during treatment 10,2123. Zhang et al23 found that a child’s OHRQoL was frequently worse during treatment (oral symptoms, functional limitations) and the greatest deterioration in OHRQoL occurs during the first month of treatment.…”
Section: Discussionsupporting
confidence: 83%
“…[91011] Evidence has shown that orthodontic treatment affects QoL and that the magnitude of the negative impact is related to the type of therapy received. [12] For example, Bernabě et al . found that adolescents wearing fixed appliances had a higher frequency of impact than those wearing removable or both types of appliances simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…[345678] The intensity of the negative impact depends on the type of therapy received. For example, Bernabe et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bernabe et al . [3] found that adolescents wearing fixed appliances had a higher frequency of impact than those wearing removable or both types of appliances simultaneously. Another study done by Miller et al .…”
Section: Introductionmentioning
confidence: 99%